The Ownability of Land: Property Right, Natural Resources and Environmental Protection - Hinchcliffe, Christopher M. (My University, 2009)
Restrictions on the kinds of things people can own and on the uses to which people can put their property is as familiar an idea as that of property itself. A consequence of this familiarity is that it is easy to overlook the reasons why we can own a sandwich but not a smile. A second consequence is that it is not always clear when or whether restrictions on how we use the things we own undermine our ownership.
In this paper, I will discuss a theory of property recently offered by James Penner. Penner seeks to replace the so-called "bundle of rights" picture of property which he claims suffers from internal conceptual tension and which offers little real help to lawmakers when it comes to making decisions about property. Penner attempts to unify the bundle of rights by focusing instead on the interest we have in owning things. It is not that we have a certain kind of right that puts us in a property relationship with something, it is that the right we have protects the interest we have in owning it.
The primary thesis of this paper is that restrictions on the use of natural resources, when they are enacted to protect the environment "for its own sake" undermine the possibility of a property relationship with those resources. Ownership is generally the right to exclusively determine the use of a thing. But when the things we 'own' have legally protected interests in how they are used, then it can no longer be said that our determination of their use is exclusive, and ownership of those things becomes impossible.
Keywords: Philosophy; Philosophy